Plasma Cytokine Profiles in Subjects with High-Functioning Autism Spectrum Disorders - Suzuki, Katsuaki (Public Library of Science, 2011)
BACKGROUND: Accumulating evidence suggests that dysregulation of the immune system is involved in the pathophysiology of autism spectrum disorders (ASD). The aim of the study was to explore immunological markers in peripheral plasma samples from non-medicated subjects with high-functioning ASD. METHODOLOGY/PRINCIPAL FINDINGS: A multiplex assay for cytokines and chemokines was applied to plasma samples from male subjects with high-functioning ASD (n = 28) and matched controls (n = 28). Among a total of 48 analytes examined, the plasma concentrations of IL-1β, IL-1RA, IL-5, IL-8, IL-12(p70), IL-13, IL-17 and GRO-α were significantly higher in subjects with ASD compared with the corresponding values of matched controls after correction for multiple comparisons. CONCLUSION/SIGNIFICANCE: The results suggest that abnormal immune responses as assessed by multiplex analysis of cytokines may serve as one of the biological trait markers for ASD.